2003
DOI: 10.1107/s0907444903001227
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a family 11 xylanase fromBacillus subtillisB230 used for paper bleaching

Abstract: Enzymes such as family 11 xylanases are increasingly being used for industrial applications. Here, the cloning, structure determination and temperature-stability data of a family 11 xylanase, Xyn11X, from the alkali-tolerant Bacillus subtilis subspecies B230 are reported. This enzyme, which degrades xylan polymers, is being produced on an industrial scale for use in the paper-bleaching industry. Xyn11X adopts the canonical family 11 xylanase fold. It has a greater abundance of side chain to side chain hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…The earlier reported superpositions 9,[18][19][20]23 were made for increasing the number of solved structures of xylanases 11. Here all available crystal structures of xylanases belonging to family 11 and currently deposited in the Protein Data Bank have been compared and superposed on XYNII molecule to illustrate the stability of the xylanase molecule of family 11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The earlier reported superpositions 9,[18][19][20]23 were made for increasing the number of solved structures of xylanases 11. Here all available crystal structures of xylanases belonging to family 11 and currently deposited in the Protein Data Bank have been compared and superposed on XYNII molecule to illustrate the stability of the xylanase molecule of family 11.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 It is worth mentioning that Moiseeva and Allaire 11 have reported on crystallization of this enzyme and its preliminary diffraction studies to a resolution as good as 0.095 nm; however, the structure determined at this resolution has not been published yet in the Protein Data Bank (PDB). Besides the structure of XYNII, several crystal structures of other xylanases from family 11 have been solved by X-ray diffraction, including the enzymes from Aspergillus kawachii, 12 Aspergillus niger, 13 Bacillus agaradhaerens, 14 Bacillus circulans, 15,16 Bacillus D3, 17 Bacillus subtilis B230, 18 Chaetomium thermophilum,…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported on kraft pulp bleaching with xylanase from diVerent microbial sources, mostly for reducing the amount of chlorine requirement in the bleaching process, kappa number reduction and brightness enhancement [5,9,18,24]. Literature on biobleaching of alternate cellulosic Wbres are scanty.…”
Section: Optimization Of Reaction Time For Biobleaching Of Banana Wbrmentioning
confidence: 99%
“…14) A significant industrial utility of some family-11 xylanases is in the biobleaching of kraft pulp. [18][19][20][21] We analyzed sugar (total and reducing) and chromophore (absorbing at 237 and 465 nm) release from EKP by rXyn11A, as described by Elegir et al 22) and Wood and Bhat, 14) to validate our TLC result with respect to EKP hydrolysis (Fig. 3).…”
Section: )mentioning
confidence: 99%